Online Independence Day Celebration: Adjusting Group Ties and Social Dynamics in Urban Area - Yudha, Reza Praditya (MediaTor (Jurnal Komunikasi), 2022)
This study examines people's engagement in the media that relates to the socio-cultural dynamic to adjust to the Covid-19 pandemic situation. This study aims to describe online activities -in the context of the 76th Indonesia's Independence Day celebration- as a form of socio-cultural mediatization. This study is using digital ethnographic methods and collects data through observations, interviews, activity participation, and documentation of the informants' conversations on WhatsApp groups. This study finds the meaning of online activities as a form of community adaptation to social situations and efforts to maintain routine, harmony, and togetherness. Online activities are a form of social transformation and a new pattern of celebrating Independence Day which is increasingly related to the practice of using digital media, especially during the Covid-19 pandemic. Online activities are also an opportunity that shifts social values that are based on togetherness in terms of time and place, into virtual presence and participation.